ANSWER
This is an ellipse. The equation is:
![\frac{(x-1)^2}{3^2}+\frac{(y+4)^2}{4^2}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-1%29%5E2%7D%7B3%5E2%7D%2B%5Cfrac%7B%28y%2B4%29%5E2%7D%7B4%5E2%7D%3D1)
EXPLANATION
We have to complete the square for each variable. To do so, we have to take the first two terms and compare them with the perfect binomial squared formula,
![(a+b)^2=a^2+2ab+b^2](https://tex.z-dn.net/?f=%28a%2Bb%29%5E2%3Da%5E2%2B2ab%2Bb%5E2)
For x we have to take 16x² and -32x. Since the coefficient of x is not 1, first, we have to factor out the coefficient 16,
![16x^2-32x=16(x^2-2x)](https://tex.z-dn.net/?f=16x%5E2-32x%3D16%28x%5E2-2x%29)
Now, the first term of the expanded binomial would be x and the second term -2x. Thus, the binomial is,
![(x-1)^2=x^2-2x+1](https://tex.z-dn.net/?f=%28x-1%29%5E2%3Dx%5E2-2x%2B1)
To maintain the equation, we have to subtract 1,
![16(x^2-2x+1-1)=16((x-1)^2-1)=16(x-1)^2-16](https://tex.z-dn.net/?f=16%28x%5E2-2x%2B1-1%29%3D16%28%28x-1%29%5E2-1%29%3D16%28x-1%29%5E2-16)
Now, we replace (16x² - 32x) from the given equation by this equivalent expression,
![16(x-1)^2-16+9y^2+72y+16=0](https://tex.z-dn.net/?f=16%28x-1%29%5E2-16%2B9y%5E2%2B72y%2B16%3D0)
The next step is to do the same for y. We have the terms 9y² + 72y. Again, since the coefficient of y² is not 1, we factor out the coefficient 9,
![9y^2+72y=9(y^2+8y)](https://tex.z-dn.net/?f=9y%5E2%2B72y%3D9%28y%5E2%2B8y%29)
Following the same reasoning as before, we have that the perfect binomial squared is,
![(y+4)^2=y^2+8y+16](https://tex.z-dn.net/?f=%28y%2B4%29%5E2%3Dy%5E2%2B8y%2B16)
Remember to subtract the independent term to maintain the equation,
![9(y^2+8y)=9(y^2+8y+16-16)=9((y+4)^2-16)=9(y+4)^2-144](https://tex.z-dn.net/?f=9%28y%5E2%2B8y%29%3D9%28y%5E2%2B8y%2B16-16%29%3D9%28%28y%2B4%29%5E2-16%29%3D9%28y%2B4%29%5E2-144)
And now, as we did for x, replace the two terms (9y² + 72y) with this equivalent expression in the equation,
![16(x-1)^2-16+9(y+4)^2-144+16=0](https://tex.z-dn.net/?f=16%28x-1%29%5E2-16%2B9%28y%2B4%29%5E2-144%2B16%3D0)
Add like terms,
![\begin{gathered} 16(x-1)^2+9(y+4)^2+(-16-144+16)=0 \\ 16(x-1)^2+9(y+4)^2-144=0 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%2016%28x-1%29%5E2%2B9%28y%2B4%29%5E2%2B%28-16-144%2B16%29%3D0%20%5C%5C%2016%28x-1%29%5E2%2B9%28y%2B4%29%5E2-144%3D0%20%5Cend%7Bgathered%7D)
Add 144 to both sides,
![\begin{gathered} 16(x-1)^2+9(y+4)^2-144+144=0+144 \\ 16(x-1)^2+9(y+4)^2=144 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%2016%28x-1%29%5E2%2B9%28y%2B4%29%5E2-144%2B144%3D0%2B144%20%5C%5C%2016%28x-1%29%5E2%2B9%28y%2B4%29%5E2%3D144%20%5Cend%7Bgathered%7D)
As we can see, this is the equation of an ellipse. Its standard form is,
![\frac{(x-h)^2}{a^2}+\frac{(y-k)^2}{b^2}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-h%29%5E2%7D%7Ba%5E2%7D%2B%5Cfrac%7B%28y-k%29%5E2%7D%7Bb%5E2%7D%3D1)
So the next step is to divide both sides by 144 and also write the coefficients as fractions in the denominator,
![\begin{gathered} \frac{16(x-1)^2}{144}+\frac{9(y+4)^2}{144}=\frac{144}{144} \\ \\ \frac{(x-1)^2}{\frac{144}{16}}+\frac{(y+4)^2}{\frac{144}{9}}=1 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Cfrac%7B16%28x-1%29%5E2%7D%7B144%7D%2B%5Cfrac%7B9%28y%2B4%29%5E2%7D%7B144%7D%3D%5Cfrac%7B144%7D%7B144%7D%20%5C%5C%20%20%5C%5C%20%5Cfrac%7B%28x-1%29%5E2%7D%7B%5Cfrac%7B144%7D%7B16%7D%7D%2B%5Cfrac%7B%28y%2B4%29%5E2%7D%7B%5Cfrac%7B144%7D%7B9%7D%7D%3D1%20%5Cend%7Bgathered%7D)
Finally, we have to write the denominators as perfect squares, so we identify the values of a and b. 144 is 12², 16 is 4² and 9 is 3²,
![\frac{(x-1)^2}{(\frac{12}{4})^2}+\frac{(y+4)^2}{(\frac{12}{3})^2}=1](https://tex.z-dn.net/?f=%5Cfrac%7B%28x-1%29%5E2%7D%7B%28%5Cfrac%7B12%7D%7B4%7D%29%5E2%7D%2B%5Cfrac%7B%28y%2B4%29%5E2%7D%7B%28%5Cfrac%7B12%7D%7B3%7D%29%5E2%7D%3D1)
Note that we can simplify a and b,
![\frac{12}{4}=3\text{ and }\frac{12}{3}=4](https://tex.z-dn.net/?f=%5Cfrac%7B12%7D%7B4%7D%3D3%5Ctext%7B%20and%20%7D%5Cfrac%7B12%7D%7B3%7D%3D4)
Hence, the equation of the ellipse is,